The Supreme Administrative Court of the Slovak Republic – the First Step Towards a Modern Justice System - Lilla Garayová (Institutiones Administrationis, 2021)
The article provides an overview of the ongoing comprehensive judicial reform in the Slovak Republic, focusing mostly on the creation of the Supreme Administrative Court, which will become the highest judicial authority in the field of administrative justice. It will also act as a disciplinary court for general court judges, prosecutors and other statutory professions. This is one of the first steps in what will be a huge undertaking – the complete reform of the Slovak justice system.